2019
DOI: 10.1007/s42770-019-00209-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromium (VI) bioremediation potential of filamentous fungi isolated from Peruvian tannery industry effluents

Abstract: The tannery is an important trade in various Peruvian regions; however, tannery effluents are a serious local environmental threat due to its highly toxics components and lack of efficient treatment. The untreated effluents produced by tannery factories in Arequipa Rio Seco Industrial Park (PIRS) have formed a lake in the region nearby. In this work, we study the capability of filamentous fungi species found in this effluents lake with potential for chromium (VI) bioremediation. Fourteen species of filamentous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Some ecological, biochemical, molecular and geneticapproaches should also be integrated for developing of novel technologies (Gorai et al 2020). Based on the recent studies, many researchers confirmed the role of Trichoderma in the bioremediation of many organic contaminants such asTNT by Trichoderma viride (Alothman et al 2020), chromium by by Trichoderma viride (Zapana-Huarache et al 2020), and copper or chromium by Trichoderma lixii CR700 Dwivedi 2019, 2021), diesel byTrichoderma harzianum strain T22 (Elshafie et al 2020), and polycyclic aromatic hydrocarbons by T. longibrachiatum (Li et al 2021).…”
Section: Trichoderma For Sustainable Agriculturementioning
confidence: 99%
“…Some ecological, biochemical, molecular and geneticapproaches should also be integrated for developing of novel technologies (Gorai et al 2020). Based on the recent studies, many researchers confirmed the role of Trichoderma in the bioremediation of many organic contaminants such asTNT by Trichoderma viride (Alothman et al 2020), chromium by by Trichoderma viride (Zapana-Huarache et al 2020), and copper or chromium by Trichoderma lixii CR700 Dwivedi 2019, 2021), diesel byTrichoderma harzianum strain T22 (Elshafie et al 2020), and polycyclic aromatic hydrocarbons by T. longibrachiatum (Li et al 2021).…”
Section: Trichoderma For Sustainable Agriculturementioning
confidence: 99%
“…Among these metals, the highest biosorption potential was shown for lead by A. fumigatus isolate K3 [107]. In another study, three fungal sp., namely Penicillium citrinum, Trichoderma viride and Penicillium sp., isolated from untreated tannery effluents were found to be highly tolerant against high concentrations, i.e., 100 mg/L of chromium IV and showed significant growth up to 250 mg/L indicating their good potential to tolerate and adapt to elevated chromium concentrations [108].…”
Section: Fungimentioning
confidence: 99%
“…Oil spills Bovio et al [134] Penicillium citrinum Chromium Zapana-Huarache et al [135] Penicillium coffeae Arsenic Bhargavi, Savitha [136] (Contd...)…”
Section: Penicillium Citreonigrummentioning
confidence: 99%